An Effort to Increase the Learning Activeness of Class VIII B Students in IPS Subjects with the Problem Solving Method at SMP Pemda 2 Kesugihan - Karina Tri Anggraeni; Beny Wijarnako Kertopati (UM Purwokerto Press, 2025)
The low learning activity of students with socialsubjects at SMP Pemda 2 Kesugihan, shows a lack of enthusiasm in participating in learning, students tend to be passive during the learning process and during the delivery of learning takes place when delivering learning material the teacher applies more conventional methods or by lecturing methods, while students listen more so that the atmosphere of learning in class becomes rigid and less interesting. The object of this research is class VIII B students with a total of 31 students. The purpose of this study was to increase student activeness in ips class VIII B. This type of research uses class action research (PTK) this research is included in the type of qualitative research in the form of PTK the method is used to overcome existing problems in the classroom. In this study using 2 cycles, the results of student activity in SMP Pemda 2 Kesugihan class VIII B with social studies subjects with population dynamics material there is an increase from cycle I and cycle II with a total of 31 students with the category of cycle I meeting 1 with an average of 56.68% with a sufficient category while with cycle I meeting 2 with an average of 71.66% with a good category and in cycle II meeting I with an average of 75 with a good category and cycle II meeting 2 with an average of 83.34 with a good category . Based on the analysis of research data, the use of the Problem Solving method is said to be successful in increasing student learning activities in class VIII B SMP Pemda 2 Kesugihan.